English for Economics Education Department Student: Case Study of Students' Perspective at University of HKBP Nommensen Pematangsiantar (UHKBPNP) - Nababan, Irene Adryani; Sinurat, Bloner; Sitanggang, Anita; Damanik, Esrayani; Simbolon, Dony Wira; Amin, Teguh Satria (International Journal of Educational Research Excellence (IJERE), 2025)
In today’s globalized world, English has become an essential tool in various academic and professional fields, including economics. This study explores the perceptions of economics students at the University of HKBP Nommensen Pematangsiantar (UHKBPNP) regarding the role and importance of English in their education and future careers. Using a descriptive qualitative approach, the study focuses on students’ experiences, challenges, and attitudes toward English language learning within the context of their economics studies. A total of 44 students of Economics Education Department participated in this case study, with data collected through structured questionnaires and analyzed using descriptive statistics. The results indicate that the majority of students recognize the critical role of English in understanding economic concepts, accessing academic resources, and participating in discussions. Students also acknowledge the significance of English proficiency for career development, particularly for job opportunities in multinational companies and international organizations. However, many students face challenges in mastering technical economic vocabulary, reading English textbooks, writing academic reports, and comprehending English lectures. The findings highlight a strong demand for more specialized English courses, such as Business English or English for Specific Purposes (ESP), to better prepare students for the linguistic demands of the global economic sector. In conclusion, the study emphasizes the need for enhanced English language instruction tailored to the specific needs of Economics Education Department students at UHKBPNP. Incorporating practical and specialized English courses into the curriculum will enable students to achieve academic success and excel in their future careers in a globalized marketplace.